2021
DOI: 10.1039/d1nj00441g
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interactions between protein coronated CdSe quantum dots and nanoplastics

Abstract: It is now established that the metastable colloidal nanoparticles (NPs) are subjected to interaction with proteins in biological media leading to the formation of protein corona on the NPs. The...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Larger agglomerated protein corona structures were also formed as a result of micron‐sized cluster formation of CdS–GT QDs with HSA in biological fluids. [ 50 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger agglomerated protein corona structures were also formed as a result of micron‐sized cluster formation of CdS–GT QDs with HSA in biological fluids. [ 50 ]…”
Section: Resultsmentioning
confidence: 99%
“…Larger agglomerated protein corona structures were also formed as a result of micron-sized cluster formation of CdS-GT QDs with HSA in biological fluids. [50] 3.3 | Fluorescence quenching and binding analysis of HSA in the presence of CdS-GT QDs/ligands…”
Section: Sensing Studiesmentioning
confidence: 99%
“…Larger agglomerated protein-corona structures were also observed in the Figure S9, which was due to micron sized cluster formation of the respective CdSe QDs in the biological matrix. [55] Fluorescence response of CdSe QDs to lomefloxacin Fluorometry is the time and cost-effective technique used in detection of antibiotics based on fluorescence probe. Before performing the detection of lomefloxacin, we have investigated the optimized conditions.…”
Section: Uv-vis Absorption Studies For Ground-state Complex Formationmentioning
confidence: 99%
“…In addition to analyzing a contaminant‘s direct impact on cells, it is vital to identify dynamic interactions that are feasible in an in vivo system. In an initial study conducted previously by our group, it was observed that functionalized PS‐beads could alter the colloidal stability of coronated CdSe quantum dots (QDs) forming large agglomerated complexes [13] …”
Section: Introductionmentioning
confidence: 99%
“…In an initial study conducted previously by our group, it was observed that functionalized PS-beads could alter the colloidal stability of coronated CdSe quantum dots (QDs) forming large agglomerated complexes. [13] In the present study, we aim to elucidate the multilayer interaction pattern of GNRs from a mixture effect perspective. Considering the wide range of biomedical applications, GNRs were selected as a model nanoparticle.…”
Section: Introductionmentioning
confidence: 99%